Institutional Repositories - Rumery, Joyce (Maine Policy Review, 2013)
Joyce Rumery discusses the opportunities presented by participation in the “Digital Commons,” a national online service (institutional repository) that allows institutions to highlight the work of faculty and students and to provide a medium for managing and preserving items such as materials from special collections.
Keywords: institutional repositories; Digital Commons; Maine